2022
DOI: 10.3390/educsci12030165
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Integrated Learning Definitions, Frameworks, and Practices in Recent Health Professions Education Literature

Abstract: International curricular redevelopment and quality improvement efforts include integration within and across disciplines as a focal point. Definitions and applications of the term ‘integration’ vary routinely in health professions education literature, weakening opportunities to enhance our educational practice through collaborative, interprofessional knowledge-sharing. This systematic review examined recent health professions education literature for reported definitions, theories or frameworks, and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In burn services in Malawi and Ethiopia, in relation to QI initiatives, major enablers included efficacious KS, whereas a negative ethos with respect to training was a main obstacle (Holden et al, 2021). Through a literature review of health professions education, KS was found to be an important factor affecting QI (Matinho et al, 2022). Besides, through empirical studies in the healthcare sector, KS has been found to be a key factor affecting QI interventions (Allen, 2016), QI awareness (Hut-Mossel et al, 2021), QI collaborative (Olsen et al, 2021), continuous QI (Laycock et al, 2018), andQIP (El Morr andJulien, 2010;Sorakraikitikul and Siengthai, 2014;Aveling et al, 2017;Hassanain, 2017;Svenningsson et al, 2019;Lebcir and James, 2021;Nelson et al, 2022).…”
Section: Knowledge-sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…In burn services in Malawi and Ethiopia, in relation to QI initiatives, major enablers included efficacious KS, whereas a negative ethos with respect to training was a main obstacle (Holden et al, 2021). Through a literature review of health professions education, KS was found to be an important factor affecting QI (Matinho et al, 2022). Besides, through empirical studies in the healthcare sector, KS has been found to be a key factor affecting QI interventions (Allen, 2016), QI awareness (Hut-Mossel et al, 2021), QI collaborative (Olsen et al, 2021), continuous QI (Laycock et al, 2018), andQIP (El Morr andJulien, 2010;Sorakraikitikul and Siengthai, 2014;Aveling et al, 2017;Hassanain, 2017;Svenningsson et al, 2019;Lebcir and James, 2021;Nelson et al, 2022).…”
Section: Knowledge-sharingmentioning
confidence: 99%
“…In burn services in Malawi and Ethiopia, in relation to QI initiatives, major enablers included efficacious KS, whereas a negative ethos with respect to training was a main obstacle (Holden et al ., 2021). Through a literature review of health professions education, KS was found to be an important factor affecting QI (Matinho et al ., 2022). Besides, through empirical studies in the healthcare sector, KS has been found to be a key factor affecting QI interventions (Allen, 2016), QI awareness (Hut-Mossel et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, anatomy educators are increasingly expected to learn, deploy, and participate in a dizzying array of innovative teaching activities (Owolabi & Bekele, 2021) as well as engage with curricular practices imposed by their institution, having to do more with considerably less in the way of time and training resources. Matinho et al (2022) report that a total of 43 distinct practices designed to achieve integrated learning, education, curriculum, or teaching were identified in 77% of the articles they reviewed.…”
Section: Reflective Practice In Anatomymentioning
confidence: 99%
“…This polar distinction divided the curriculum and stratified the linear timescale used in medical education since the historic 1910 reforms of Abraham Flexner (Flexner, 1910; Duffy, 2011). Curriculum research over the last several decades has been aiming for integration, despite the routine variation of applications and definitions of the term as pointed out by Matinho et al (2022) in their recent systematic review of integrated learning definitions. Without unified definitions, the term ‘integration’ has become more of a buzzword (Brauer & Ferguson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most common form of reflective practice in medical education is reflective writing (RW) [ 25 ]. Identified as one of the distinct approaches used to achieve integrated learning, education, curriculum and teaching [ 26 ], RW already occupies a central role in guiding and supporting longitudinal professional development [ 27 29 ]. Its ability to enhance self-monitoring and self-regulation of decisional paradigms and conduct has earned RW a key role in competency-based medical practice and continuing professional development [ 30 – 36 ].…”
Section: Introductionmentioning
confidence: 99%